Penerapan Battery Test sebagai Rekomendasi Jurusan di Perguruan Tinggi - Esty Aryani Safithry; Indah Sari Dewi; Fathul Zannah; Amelia Dwi Astuti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The potential of students can be identified by carrying out psychological tests that describe students' personalities. There are 3 components of the test given, namely the integration test (IST), job interest (Kuder test), and personality test (EPPS). The combination of these three tests is called a battery test which results in a psychological report containing a psychogram regarding personal aspects, psychological descriptions, strengths, and weaknesses as well as recommendations for the appropriate field of work. This activity is planned to be carried out in non-school institutions such as courses or tutoring institutions. Based on the evaluation of self-assessment, it shows that participants are able to understand their personal condition along with their strengths and weaknesses, personal areas that need to be developed, and recommendations for higher education majors that are in accordance with their talents, personal interests of participants, evaluation of assessments of training activities shows the results that this training provides benefits to participants, especially regarding college recommendations and assessment of presenters where the presenters are considered good enough in delivering activity material.